Audience segmentation analysis of public intentions to get a COVID-19 vaccine in Australia. (May 2023) - Thaker, Jagadish; Richardson, Lucy M.; Holmes, David C.
While previous studies provide broad categories of the public who intend to get a COVID-19 vaccine, few systematically segment and help understand and engage with distinct publics to improve COVID-19 vaccine uptake. Using data from a national sample of the Australian public ( N = 1054) and using measures primarily based on the Theory of Planned Behaviour, a latent class analysis of 16 items was undertaken to identify COVID-19 audience segments for potential future message targeting. We found five different segments of COVID-19 vaccine intentions: vaccine enthusiasts (28%), supporters (26%), socials (20%), hesitant (15%) and sceptics (10%). These five audience segments also differ on demographic variables and their level of trust in mainstream media, scientists and health experts, social media and family and friends. Understanding the COVID-19 vaccine attitudinal and information-seeking characteristics of these sub-publics will help inform appropriate messaging campaigns.